Mobile augmented reality for smart pet - Ooi, Shion Yeing (2019)
Mobile Augmented Reality (AR) for Smart Pet is an augmented reality virtual pet simulation game application. The name of this game application is called Sorumeito, which is translate from the word “soulmate” to Japanese word. The pet in Sorumeito called Soru. The application named like this because people who loneliness or depression can have companion with them and overcome the hard time together. The companion is like a soulmate that can heal their soul and heart or even can just play for fun. Especially for the students which include primary students, secondary students, and university students are facing the same problems which are easy get stress from their academic study. The main purpose of this application is some of people are not effort to buy a real pet thus this application can stimulate a virtual pet for them to play. Thus, user can save a lot of money, time and space when they want to have a real pet compared to virtual pet. Virtual pet no need fed by real food, would not get ill, no need bath for them and even not occupied the space of owner houses, it just occupied the space of the phone. In order to let the pet can be more reality, this game application is developed by using unity game engine and combine with AR technique which is Vuforia. Vuforia is an augmented reality software development kit (SDK) for mobile devices thus author can bring virtual object to real world. Furthermore, artificial intelligent part includes voice recognition and face detection will be added into this game so that owner can speak with the pet and the pet can detect their own owner face expression, then the virtual pet can make some animation based on the expression.